# 4.10 Antiderivatives  (Page 3/10)

 Page 3 / 10
Integration formulas
Differentiation Formula Indefinite Integral
$\frac{d}{dx}\left(k\right)=0$ $\int kdx=\int k{x}^{0}dx=kx+C$
$\frac{d}{dx}\left({x}^{n}\right)=n{x}^{n-1}$ $\int {x}^{n}dn=\frac{{x}^{n+1}}{n+1}+C$ for $n\ne \text{−}1$
$\frac{d}{dx}\left(\text{ln}|x|\right)=\frac{1}{x}$ $\int \frac{1}{x}dx=\text{ln}|x|+C$
$\frac{d}{dx}\left({e}^{x}\right)={e}^{x}$ $\int {e}^{x}dx={e}^{x}+C$
$\frac{d}{dx}\left(\text{sin}\phantom{\rule{0.1em}{0ex}}x\right)=\text{cos}\phantom{\rule{0.1em}{0ex}}x$ $\int \text{cos}\phantom{\rule{0.1em}{0ex}}x\phantom{\rule{0.1em}{0ex}}dx=\text{sin}\phantom{\rule{0.1em}{0ex}}x+C$
$\frac{d}{dx}\left(\text{cos}\phantom{\rule{0.1em}{0ex}}x\right)=\text{−}\text{sin}\phantom{\rule{0.1em}{0ex}}x$ $\int \text{sin}\phantom{\rule{0.1em}{0ex}}x\phantom{\rule{0.1em}{0ex}}dx=\text{−}\text{cos}\phantom{\rule{0.1em}{0ex}}x+C$
$\frac{d}{dx}\left(\text{tan}\phantom{\rule{0.1em}{0ex}}x\right)={\text{sec}}^{2}x$ $\int {\text{sec}}^{2}x\phantom{\rule{0.1em}{0ex}}dx=\text{tan}\phantom{\rule{0.1em}{0ex}}x+C$
$\frac{d}{dx}\left(\text{csc}\phantom{\rule{0.1em}{0ex}}x\right)=\text{−}\text{csc}\phantom{\rule{0.1em}{0ex}}x\phantom{\rule{0.1em}{0ex}}\text{cot}\phantom{\rule{0.1em}{0ex}}x$ $\int \text{csc}\phantom{\rule{0.1em}{0ex}}x\phantom{\rule{0.1em}{0ex}}\text{cot}\phantom{\rule{0.1em}{0ex}}x\phantom{\rule{0.1em}{0ex}}dx=\text{−}\text{csc}\phantom{\rule{0.1em}{0ex}}x+C$
$\frac{d}{dx}\left(\text{sec}\phantom{\rule{0.1em}{0ex}}x\right)=\text{sec}\phantom{\rule{0.1em}{0ex}}x\phantom{\rule{0.1em}{0ex}}\text{tan}\phantom{\rule{0.1em}{0ex}}x$ $\int \text{sec}\phantom{\rule{0.1em}{0ex}}x\phantom{\rule{0.1em}{0ex}}\text{tan}\phantom{\rule{0.1em}{0ex}}x\phantom{\rule{0.1em}{0ex}}dx=\text{sec}\phantom{\rule{0.1em}{0ex}}x+C$
$\frac{d}{dx}\left(\text{cot}\phantom{\rule{0.1em}{0ex}}x\right)=\text{−}{\text{csc}}^{2}x$ $\int {\text{csc}}^{2}x\phantom{\rule{0.1em}{0ex}}dx=\text{−}\text{cot}\phantom{\rule{0.1em}{0ex}}x+C$
$\frac{d}{dx}\left({\text{sin}}^{-1}x\right)=\frac{1}{\sqrt{1-{x}^{2}}}$ $\int \frac{1}{\sqrt{1-{x}^{2}}}={\text{sin}}^{-1}x+C$
$\frac{d}{dx}\left({\text{tan}}^{-1}x\right)=\frac{1}{1+{x}^{2}}$ $\int \frac{1}{1+{x}^{2}}dx={\text{tan}}^{-1}x+C$
$\frac{d}{dx}\left({\text{sec}}^{-1}|x|\right)=\frac{1}{x\sqrt{{x}^{2}-1}}$ $\int \frac{1}{x\sqrt{{x}^{2}-1}}dx={\text{sec}}^{-1}|x|+C$

From the definition of indefinite integral of $f,$ we know

$\int f\left(x\right)dx=F\left(x\right)+C$

if and only if $F$ is an antiderivative of $f.$ Therefore, when claiming that

$\int f\left(x\right)dx=F\left(x\right)+C$

it is important to check whether this statement is correct by verifying that ${F}^{\prime }\left(x\right)=f\left(x\right).$

## Verifying an indefinite integral

Each of the following statements is of the form $\int f\left(x\right)dx=F\left(x\right)+C.$ Verify that each statement is correct by showing that ${F}^{\prime }\left(x\right)=f\left(x\right).$

1. $\int \left(x+{e}^{x}\right)dx=\frac{{x}^{2}}{2}+{e}^{x}+C$
2. $\int x{e}^{x}dx=x{e}^{x}-{e}^{x}+C$
1. Since
$\frac{d}{dx}\left(\frac{{x}^{2}}{2}+{e}^{x}+C\right)=x+{e}^{x},$

the statement
$\int \left(x+{e}^{x}\right)dx=\frac{{x}^{2}}{2}+{e}^{x}+C$

is correct.
Note that we are verifying an indefinite integral for a sum. Furthermore, $\frac{{x}^{2}}{2}$ and ${e}^{x}$ are antiderivatives of $x$ and ${e}^{x},$ respectively, and the sum of the antiderivatives is an antiderivative of the sum. We discuss this fact again later in this section.
2. Using the product rule, we see that
$\frac{d}{dx}\left(x{e}^{x}-{e}^{x}+C\right)={e}^{x}+x{e}^{x}-{e}^{x}=x{e}^{x}.$

Therefore, the statement
$\int x{e}^{x}dx=x{e}^{x}-{e}^{x}+C$

is correct.
Note that we are verifying an indefinite integral for a product. The antiderivative $x{e}^{x}-{e}^{x}$ is not a product of the antiderivatives. Furthermore, the product of antiderivatives, ${x}^{2}{e}^{x}\text{/}2$ is not an antiderivative of $x{e}^{x}$ since
$\frac{d}{dx}\left(\frac{{x}^{2}{e}^{x}}{2}\right)=x{e}^{x}+\frac{{x}^{2}{e}^{x}}{2}\ne x{e}^{x}.$

In general, the product of antiderivatives is not an antiderivative of a product.

Verify that $\int x\phantom{\rule{0.1em}{0ex}}\text{cos}\phantom{\rule{0.1em}{0ex}}x\phantom{\rule{0.1em}{0ex}}dx=x\phantom{\rule{0.1em}{0ex}}\text{sin}\phantom{\rule{0.1em}{0ex}}x+\text{cos}\phantom{\rule{0.1em}{0ex}}x+C.$

$\frac{d}{dx}\left(x\phantom{\rule{0.1em}{0ex}}\text{sin}\phantom{\rule{0.1em}{0ex}}x+\text{cos}\phantom{\rule{0.1em}{0ex}}x+C\right)=\text{sin}\phantom{\rule{0.1em}{0ex}}x+x\phantom{\rule{0.1em}{0ex}}\text{cos}\phantom{\rule{0.1em}{0ex}}x-\text{sin}\phantom{\rule{0.1em}{0ex}}x=x\phantom{\rule{0.1em}{0ex}}\text{cos}\phantom{\rule{0.1em}{0ex}}x$

In [link] , we listed the indefinite integrals for many elementary functions. Let’s now turn our attention to evaluating indefinite integrals for more complicated functions. For example, consider finding an antiderivative of a sum $f+g.$ In [link] a. we showed that an antiderivative of the sum $x+{e}^{x}$ is given by the sum $\left(\frac{{x}^{2}}{2}\right)+{e}^{x}$ —that is, an antiderivative of a sum is given by a sum of antiderivatives. This result was not specific to this example. In general, if $F$ and $G$ are antiderivatives of any functions $f$ and $g,$ respectively, then

$\frac{d}{dx}\left(F\left(x\right)+G\left(x\right)\right)={F}^{\prime }\left(x\right)+{G}^{\prime }\left(x\right)=f\left(x\right)+g\left(x\right).$

Therefore, $F\left(x\right)+G\left(x\right)$ is an antiderivative of $f\left(x\right)+g\left(x\right)$ and we have

$\int \left(f\left(x\right)+g\left(x\right)\right)dx=F\left(x\right)+G\left(x\right)+C.$

Similarly,

$\int \left(f\left(x\right)-g\left(x\right)\right)dx=F\left(x\right)-G\left(x\right)+C.$

In addition, consider the task of finding an antiderivative of $kf\left(x\right),$ where $k$ is any real number. Since

$\frac{d}{dx}\left(kf\left(x\right)\right)=k\frac{d}{dx}F\left(x\right)=k{F}^{\prime }\left(x\right)$

for any real number $k,$ we conclude that

$\int kf\left(x\right)dx=kF\left(x\right)+C.$

These properties are summarized next.

## Properties of indefinite integrals

Let $F$ and $G$ be antiderivatives of $f$ and $g,$ respectively, and let $k$ be any real number.

Sums and Differences

$\int \left(f\left(x\right)\text{±}g\left(x\right)\right)dx=F\left(x\right)\text{±}G\left(x\right)+C$

Constant Multiples

$\int kf\left(x\right)dx=kF\left(x\right)+C$

From this theorem, we can evaluate any integral involving a sum, difference, or constant multiple of functions with antiderivatives that are known. Evaluating integrals involving products, quotients, or compositions is more complicated (see [link] b. for an example involving an antiderivative of a product.) We look at and address integrals involving these more complicated functions in Introduction to Integration . In the next example, we examine how to use this theorem to calculate the indefinite integrals of several functions.

any genius online ? I need help!!
Pina
need to learn polynomial
Zakariya
i will teach...
nandu
I'm waiting
Zakariya
need help on real analysis
Guzorochi
evaluate the following computation (x³-8/x-2)
teach me how to solve the first law of calculus.
what is differentiation
f(x) = x-2 g(x) = 3x + 5 fog(x)? f(x)/g(x)
fog(x)= f(g(x)) = x-2 = 3x+5-2 = 3x+3 f(x)/g(x)= x-2/3x+5
diron
pweding paturo nsa calculus?
jimmy
how to use fundamental theorem to solve exponential
find the bounded area of the parabola y^2=4x and y=16x
what is absolute value means?
Chicken nuggets
Hugh
🐔
MM
🐔🦃 nuggets
MM
(mathematics) For a complex number a+bi, the principal square root of the sum of the squares of its real and imaginary parts, √a2+b2 . Denoted by | |. The absolute value |x| of a real number x is √x2 , which is equal to x if x is non-negative, and −x if x is negative.
Ismael
find integration of loge x
find the volume of a solid about the y-axis, x=0, x=1, y=0, y=7+x^3
how does this work
Can calculus give the answers as same as other methods give in basic classes while solving the numericals?
log tan (x/4+x/2)
Rohan
Rohan
y=(x^2 + 3x).(eipix)
Claudia
Ismael
A Function F(X)=Sinx+cosx is odd or even?
neither
David
Neither
Lovuyiso
f(x)=1/1+x^2 |=[-3,1]
apa itu?
fauzi
determine the area of the region enclosed by x²+y=1,2x-y+4=0
Hi
MP
Hi too
Vic
hello please anyone with calculus PDF should share
Which kind of pdf do you want bro?
Aftab
hi
Abdul
can I get calculus in pdf
Abdul
explain for me
Usman
okay I have such documents
Fitzgerald
Hamza